INVESTMENT PROJECT ANALYSIS OF RETAINING WALL FOR OPTIMIZING COAL PIT C2HU SAMBARATA MINING OPERATION IN PT BC - Sebastian, Ichsan
One of the mining operations held by PT Berau Coal is the Sambarata Mine Operation (SMO), where the C2HU Pit is one of four significant PITs that will be mined with priority in 2022. The C2HU pit holds 6.4 million tonnes of coal reserves with an average calorific content of 5900 cal/gr. With a traditional cut and fill design, very gentle slopes are required to achieve good slope stability because the C2HU pit is situated in a swampy area with a depth of 15 meters and is close to the Sambarata River, a third order river with a river width of 20 meters and a tidal height difference of up to 7 m that will make a loss of coal reserves in the C2HU Pit. With a total budget of $7 million needed for the initial project capital, retaining walls built using the Secant Pile method are one of the enhancements implemented to optimize coal mining in the C2HU Pit. The retaining wall is constructed utilizing closely spaced borepiles, allowing a borepile with a diameter of 1180 mm to resist the lateral stresses imposed by swamp materials, river embankments, and planned haulage highways. The secant pile technique can make the mine's overall slope more upright than the initial geotechnical suggestion, which was formed with a 6-degree angle; a secant pile can transform the swamp angle into a 90-degree angle. This helped to maximize 1.13 million tonnes of extra coal reserves. It's crucial that project stability and financial projections are reliable. A thorough approach is anticipated to be used to provide sustainable solutions when implementing this retaining wall project, including appropriate capital budgeting synergy, sensitivity analysis of all factors, including community prices of coal, production, and inflation, and risk management. The study's findings demonstrate that retaining wall investments are feasible with an NPV of 53 million US dollars by highlighting the coal price factor as the variable that is most sensitive to the investment.